The accuracy of multiple regression models for predicting the individual risk of recurrent lateral patellar dislocation - Jiang Yu; Yijin Li; Kaibo Zhang; Runze Yang; Xiaolong Yang; Meng Gong; Cheng Long; Weili Fu (BMC Musculoskeletal Disorders, 2023)
Abstract Background Recurrent lateral patellar dislocation (RLPD) poses a significant threat to patients’ quality of life due to knee pain, patellofemoral cartilage damage, and potential traumatic arthritis. Predictive scoring systems have been developed to assess the risk of RLPD; however, their relative accuracy remains uncertain. Purpose To investigate the accuracy of the multiple regression models to predict the individual risk of recurrent LPD. Methods The Patellar Instability probability calculator (PIP), Recurrent Instability of the Patella Score (RIP), and Patellar Instability Severity Score (PIS) scoring rules were measured in 171 patients with a history of patellar dislocation and 171 healthy individuals. Three prediction models were calculated based on the data to predict the risk of recurrent lateral patellar dislocation. The inter-observer and intra-observer reliability of each measurement parameter was evaluated. The predictive capacity of the three-prediction model was investigated using the receiver operating characteristic curve. Results In the case group of 171 patients, PIS accurately predicted recurrent lateral Patella dislocation in 143 patients. RIP was 96, and PIP was 83. The positive predictive values were 92.9%, 64%, and 68% respectively. In the control group of 171 patients, the PIS was validated in 160 patients who would not experience dislocations. RIP was 117, and PIP was 50. The negative predictive values were 85.1%, 60.9%, and 36.2%, respectively. The area under the curve score for the PIS was 0.866, and the RIP was 0.673. the PIP was 0.678. Conclusion RIP and PIP did not work to predict LPD. PIS can accurately predict recurrent lateral patellar dislocation. It can aid doctors in making treatment decisions. Level of evidence Level III, retrospective comparative study.